Organizational fit : key issues and new directions - Kristof-Brown, Amy L.; Billsberry, Jon (Chichester, West Sussex : Wiley-Blackwell, 2013)
'An ambitious survey of the field, by an international group of scholars, that looks toward the future of person-organization fit. Explores how people form their impressions of fit and the impact these have on their behavior, and how companies can maximize fit Includes multiple perspectives on the topic of how people fit into organizations, discussing issues across the field and incorporating insights from related disciplines Actively encourages scholars to take part in organizational fit research, drawing on workshops and symposia held specially for this book to explore some of the creative directions that the field is taking into the future'--
'Individuals and organizations are most effective when their values, needs, and interests are aligned. Person-organization fit directly affect organizational and individual effectiveness. Organizational Fit surveys the field of person-organization fit, discussing both classic perspectives and newer approaches. Covering topics such as how fit and misfit develop, how fit changes over time, how fit influences motivation, and the effect of cultural factors, contributors to this book integrate these ideas with concepts from related fields and discuss new directions for research'--
Includes bibliographical references and index.
Keywords: Organizational behavior; Corporate culture